The role of BUMDes in Community Empowerment in Salamjaya Village, Pabuaran District, Subang Regency - Achmad, Willya; Fadlurrohim, Ishak (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
BUMdes (Village Owned Enterprises) is a village business institution managed by the community and village government in an effort to strengthen the economy and is formed based on the needs and potential of the village. It is hoped that all the resources owned by the village can be empowered by the villagers themselves to increase the village's original income, so that it can be independent. Therefore this study aims to analyze the role of BUMDes in community empowerment in Salamjaya Village, Pabuaran District, Subang Regency, West Java. This research uses a qualitative approach with a descriptive method. The results of this study are the process of empowering the community's economy carried out by BUMdes Salamjaya, namely by providing capital to the community, marketing, partnerships and institutional strengthening and the impact of the existence of BUMdes is increasing business capital, increasing community production, ease of obtaining agricultural facilities, increasing community income, and social life.